Analisis Profitabilitas Dan Likuiditas Terhadap Nilai Perusahaan Dengan Harga Saham Sebagai Variabel Moderasi Pada Perusahaan Food And Beverages Yang Terdaftar Di Bursa Efek Indonesia Periode 2020–2024 - Khairun Nisa (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the effect of profitability and liquidity on firm value with stock price as a moderating variable in food and beverages companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using panel data regression analysis. The sampling technique used purposive sampling, resulting in 31 companies with 155 panel observations. Data analysis was conducted using Eviews 13 through model selection tests including Common Effect Model, Fixed Effect Model, and Random Effect Model. The results indicate that profitability proxied by Return on Assets (ROA) does not have a significant effect on firm value (probability 0.8596 > 0.05). Liquidity proxied by Current Ratio (CR) also does not significantly affect firm value (probability 0.3204 > 0.05). However, stock price significantly moderates the relationship between profitability and firm value (probability 0.0344 < 0.05). In contrast, stock price does not moderate the relationship between liquidity and firm value (probability 0.8690 > 0.05). These findings suggest that in the food and beverages sector, stock price strengthens the influence of profitability on firm value but does not strengthen the influence of liquidity on firm value.